Psychological variables associated with quality of life following primary treatment for head and neck cancer: a systematic review of the literature from 2004 to 2015. Issue 2 (26th February 2016) - Dunne, Simon; Mooney, Orla; Coffey, Laura; Sharp, Linda; Desmond, Deirdre; Timon, Conrad; O'Sullivan, Eleanor; Gallagher, Pamela
Abstract: Objective: There has been a recent proliferation of research on quality of life (QoL) in head and neck cancer (HNC). The objective of this review was to systematically examine the evidence on psychological factors associated with QoL outcomes for HNC survivors in the post‐treatment period published during 2004–2015. Methods: Five databases were searched for studies investigating psychological factors associated with QoL in HNC survivors. Empirical studies published between January 2004 and June 2015 were included if they measured QoL as an outcome following treatment using a reliable and valid measure, examined its association with at least one psychological factor and included at least 50 HNC survivors. Results: Twenty‐four publications describing 19 studies (9 cross‐sectional, 10 prospective) involving 2, 263 HNC survivors were included. There was considerable heterogeneity in study design and diversity in measurement and analysis. Distress‐related variables (depression, anxiety, distress) were most frequently investigated, and mostly reported negative associations with QoL outcomes. Associations were also observed between other psychological factors (e.g., coping, neuroticism and fear of recurrence) and QoL. Conclusions: Several psychological factors predict QoL among HNC survivors who have completed treatment. Routine screening and early interventions that target distress could improve HNC survivors' QoL following treatment. Longitudinal and population‐based studies incorporating more systematic and standardised measurement approaches are needed to better understand relationships between psychological factors and QoL and to inform the development of intervention and supportive care strategies.Copyright © 2016 John Wiley & Sons, Ltd.